Work-related stress in midlife and all-cause mortality: can sense of coherence modify this association? - Nilsen, Charlotta; Andel, Ross; Fritzell, Johan; Kåreholt, Ingemar (European journal of public health, 2016)
BACKGROUND: Survival reflects the accumulation of multiple influences experienced over the life course. Given the amount of time usually spent at work, the influence of work may be particularly important. We examined the association between work-related stress in midlife and subsequent mortality, investigating whether sense of coherence modified the association. METHODS: Self-reported work-related stress was assessed in 1393 Swedish workers aged 42-65 who participated in the nationally representative Level of Living Survey in 1991. An established psychosocial job exposure matrix was applied to measure occupation-based stress. Sense of coherence was measured as meaningfulness, manageability and comprehensibility. Mortality data were collected from the Swedish National Cause of Death Register. Data were analyzed with hazard regression with Gompertz distributed baseline intensity. RESULTS: After adjustment for socioeconomic position, occupation-based high job strain was associated with higher mortality in the presence of a weak sense of coherence (HR, 3.15; 1.62-6.13), a result that was stronger in women (HR, 4.48; 1.64-12.26) than in men (HR, 2.90; 1.12-7.49). Self-reported passive jobs were associated with higher mortality in the presence of a weak sense of coherence in men (HR, 2.76; 1.16-6.59). The link between work stress and mortality was not significant in the presence of a strong sense of coherence, indicating that a strong sense of coherence buffered the negative effects of work-related stress on mortality. CONCLUSIONS: Modifications to work environments that reduce work-related stress may contribute to better health and longer lives, especially in combination with promoting a sense of coherence among workers.
Keywords: Sex Factors; Švédsko; mortalita; Humans; lidé středního věku; Sweden; socioekonomické faktory; Occupational Stress; Female; rizikové faktory; Aged; dospělí; věkové faktory; senioři; lidé; Sense of Coherence; Mortality; sexuální faktory; Socioeconomic Factors; Adult; ženské pohlaví; pracovní stres; Male; Middle Aged; životní smysluplnost; Age Factors; mužské pohlaví; Risk Factors